A Review of Recent Development in Smart Grid and Micro-Grid Laboratories - Shamshiri, Meysam; Gan, Chin Kim; Ab Ghani, Mohd Ruddin (2012)

(untitled)
In recent decades, smart grid have become increasingly attractive to both energy producers and consumers. Amongst the main challenges for the successful realization of smart grid includes the integration of renewable energy resources, real time demand response and management of intermittent energy resources. Apart from smart grid, the development of micro-grids should take into consideration of issues such as the system performance, modeling, monitoring and controlling of the micro-grids. In particular, the recent advancements in information and communication technologies (ICTs) could facilitate the effective development of the future micro-grid system. This paper presents an overview of smart grids features and highlights the recent development of micro-grid laboratories in Europe, US and Japan.